Measuring and improving designer hazard recognition skill: Critical competency to enable prevention through design. (February 2016) - Hallowell, Matthew R.; Hansen, Daniel
Highlights: Approximately 25% of construction hazards are unidentifiable in design. Designers are capable of identifying 38% of construction hazards from design documents. Designer hazard recognition skill is improved by 27% through energy mnemonics. Hazard recognition skill is 45% greater for designers with past construction experience. Abstract: The construction industry has long accounted for one of the highest injury and fatality rates of any single-service industry. Within the construction industry, a promising technique is construction hazard prevention through design (CHPtD). Logically, CHPtD is only effective to the extent that construction hazards have emerged and are recognizable during the design phase. The objectives of this study were to measure: (1) the extent that construction hazards are apparent or recognizable during design; (2) the hazard recognition skill of designers; and (3) the extent to which hazard recognition skill can be improved in design through training and mnemonics. A multi-phase experiment was designed to identify 12 representative construction modules; observe the construction of these modules and conduct interviews to determine hazards present; obtain the design documents for the modules observed; and assess the ability of 17 designers to identify the hazards using only design documents. The results of the experiment indicated that approximately 25% of all hazards are latent in design and, of those hazards that are patent, the average designer hazard recognition skill was 51%. Further, the hazard recognition skill of designers with construction field experience was, on average, 45% higher than designers with no construction field experience ( p  = 0.02). Finally, a brief introduction to the Haddon energy mnemonic increased designer's hazard recognition skill by an average of 27% ( p  = 0.001). Future research is suggested to determine the potential impact of emerging technologies on hazard recognition skill including three-dimensional printing and virtual design and construction software.